2D & 3D-QSAR Study on Novel Piperidine and Piperazine Derivatives as Acetylcholinesterase Enzyme Inhibitors - Nazari, Maryam; Tabatabai, Sayyed A.; Rezaee, Elham (Current Computer - Aided Drug Design, 2018)
Introduction: Acetylcholinesterase enzyme (AChE) is the main target in Alzheimer's disease therapy and designing of novel AChE inhibitors is a great deal of attention. Methods: In this study, 2D-QSAR and 3D-QSAR models were generated using stepwise multiple linear regressions (SW-MLR) and comparative molecular field analysis (CoMFA) respectively. Results: It was found that CoMFA model with r2 of 0.947 for the training set and r2 of 0.816 for the test set is more favorable than model which is established by SW-MLR method with r2 =0.825 and r2pred =0.778 in 2D-QSAR. Conclusion: In addition, obtaining models were validated by cross validation with cut off values of q2 > 0.5 and r2pred > 0.6.
Keywords: Acetylcholinesterase